Multiparametric optimization for reduced condenser cooling water consumption in a degraded combined cycle gas turbine power plant from a water-energy nexus perspective. (15th December 2021) - Jamil, Ahmad; Javed, Adeel; Wajid, Abdul; Zeb, Muhammad Omar; Ali, Majid; Khoja, Asif Hussain; Imran, Muhammad
Highlights: Probabilistically modeled combined cycle power plant with measurement uncertainties. Exergetic performance comparison under 24-hour performance variations. Tri-parametric condenser cooling water consumption optimization using Cycle-Tempo. Condenser performance maps for optimum combined cycle power plant operation. Abstract: The Water-Energy Nexus is gaining considerable interest with growing environmental concerns, especially in developing countries such as Pakistan that are now under a state of water stress. Thermal power plants consume large amounts of freshwater, thereby making their water usage optimization immensely important. For potential repowering featuring reduced cooling water consumption, a clear understanding of the influence of key condenser parameters on the power plant is required. This study investigates a degraded combined cycle gas turbine power plant for reduced cooling water usage from a repowering perspective. The degraded power plant under consideration draws 13% more freshwater for recirculation-based cooling from a canal linked with the River Indus in Pakistan. The power plant has been modeled using 120 h of real-time probabilistic data at baseload by generating three study cases stemming from 24-hour parametric variations. The commercial tool Cycle-Tempo has been deployed for modeling and simulating the power plant performance with the incorporation of physical uncertainties and errors originating from the measurement sensors. The model is validated and compared with the 23 years old design case data to highlight the degradations via an exergy analysis. A tri-parametric optimization is later performed to reduce the cooling water consumption through specialized performance maps that relate exergy, low-pressure section steam turbine performance, and condenser performance to highlight potential repowering opportunities while retaining the baseload performance. The optimized cases result in approximately 9.5–11.0% lesser water consumption in terms of mass flow rate while retaining the baseload performance and key heat recovery steam generator operating points.